A biographical note on the composer António de Oliveira - Henriques, Luís (2021)
António de Oliveira was a Portuguese composer active in the last decades of the sixteenth century. He was a pupil of Manuel Mendes at Évora and made his musical career in the church of São Julião in Lisbon moving afterwards to Rome, where he died. Like Manuel Mendes, his musical production is scarce. This brief post aims to summarize what is known so far of his life and works.